Food diversity and consumption of ultra-processed food in the complementary feeding: National Health Survey, Brazil, 2013 (Research, Society and Development, 2021)
Objective: To assess food diversity and absence of consumption of ultra-processed foods in complementary feeding of Brazilian children aged between six and 24 months according to socio-demographic variables. Methods: It is a cross-sectional study that analyzed data from the National Health Survey, 2013. The food diversity and ultra-processed foods consumption were evaluated separately and together. The joint analysis was measured by score, considering the consumption of each food group that constituting food diversity, as well as the absence by each of ultra-processed foods.  It was estimated prevalence, means score and confidence intervals (95%). Socio-demographic variables analyzed: gender, race, household situation, macro-regions and household conditions. Results: Of the 3701 eligible children, only 3.8% had nutritional adequacy (food diversity and absence of ultra-processed foods), 48.8 % had food diversity, and 15.7 % did not consume ultra-processed foods. Children with low socioeconomic status had a lower score on the nutritional adequacy and a lower prevalence of food diversity and a higher prevalence of ultra-processed foods consumption. Conclusions: A large portion of Brazilian children have low feeding diversity and consume ultra-processed foods, with inequalities related to the socioeconomic status and macro-region.  Public policies and health care actions must consider these differences to reduce the disparities.